2005
DOI: 10.1111/j.1467-8535.2005.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

‘The visual helps me understand the complicated things’: pupil views of teaching and learning with interactive whiteboards

Abstract: Kate Wall is a research associate in the Centre for Learning and Teaching at Newcastle University. She has a particular interest in gathering pupils' views of learning and their thinking about learning in different contexts, in particular, how ICT can facilitate pupil reflection and how metacognitive talk can be initiated. AbstractThis study is one element of a government-sponsored evaluation into the introduction of interactive whiteboards (IWBs) to Years 5 and 6 in English primary schools. This element of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(103 citation statements)
references
References 10 publications
(10 reference statements)
5
94
0
4
Order By: Relevance
“…IWBs can initiate and facilitate learning and metacognition process effectively through visual and verbal-social features of the built-in software and hardware technology, which is being presented through color and movement, and being viewed by the majority of students positively, for many different reasons such as the visual display of information, the use of games, the concentration and the use of the board by the students themselves [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IWBs can initiate and facilitate learning and metacognition process effectively through visual and verbal-social features of the built-in software and hardware technology, which is being presented through color and movement, and being viewed by the majority of students positively, for many different reasons such as the visual display of information, the use of games, the concentration and the use of the board by the students themselves [33].…”
Section: Discussionmentioning
confidence: 99%
“…IWBs aid students' concentration and have an impact on preferred approaches to learning such as imagination, demonstration and metacognition [24].…”
Section: Iwbs' Impact On Adhd Studentsmentioning
confidence: 99%
“…Furthermore, of the 15 reviewed syntheses, only four included a detailed description of the research methodology (DiGregorio & Sobel-Lojeski, 2010;Golonka et al, 2012;Saltan et al, 2009;Twiner et al, 2010), indicating a lack of rigor. Overall, these studies and meta-analyses mentioned two potential benefits of the IWB: better presentation of certain theoretical content using multisensorial techniques (Saltan et al, 2009), but at the same time using a lecture-style approach (see Littleton, 2010); and higher student interest, at least in the short term (see Balta & Duran, 2015;DiGregorio & Sobel-Lojeski, 2010;Wall et al, 2005). Greater student motivation (see also Higgins et al, 2007Higgins et al, , 2010Hall & Higgins, 2005) was the most frequent finding across the studies, although appetite for the IWB appears to wane over time (see Balta & Duran, 2015;Dostal, 2011;Türel, 2010).…”
Section: Theoretical Framework What Does the Research Say About The Imentioning
confidence: 99%
“…By doing so, it also improves students' academic performance and concentration (Murcia, 2008;Terreni, 2010;Wall, Higgins, & Smith, 2005). Talley, Lancy & Lee (1997) found that preschoolers who had read electronic picture books at home demonstrate more willingness to read.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the use of the interactive whiteboard to present diverse information is attractive to students and enhances their concentration. It also increases students' interest in learning and supports their construction of knowledge (Hall & Higgins, 2005;Schmid, 2008;Slay et al, 2008;Wall et al, 2005). Students hold positive attitudes toward the interactive whiteboard, while teachers can use it to create a lively learning environment and make learning activities more exciting (Gatlin, 2004).…”
Section: Introductionmentioning
confidence: 99%